Socio spatial dimensions of rural housing in Mexico city. The case of Milpa Alta - Torres Veytia, Eduardo (Revista INVI, 2011)
Based on the analysis of housing characteristics, this article is the ? rst part of a study focused on habitability conditions and quality of life of residents from Milpa Alta, Mexico City. In this analysis, it is important to show the type of housing that has been built by people from Milpa Alta, as well as organization, spatial distribution and identities associated to the community; in other words, this paper aims to show rural housing built by their inhabitants as a result of speci? c needs that express the construction of an environment that should be regarded as a way of life by any instrument of public policy.